Press and the succession debate in ZANU-PF. A Look at Press Coverage of the Debate on President Robert Mugabe's succession within ZANU-PF Party in Zimbabwe - Mapuwei, Nyasha; Orina, Gladyse K. (International Institute for Science, Technology and Education, 2019)
Zimbabwe has been ruled by President Robert Mugabe and his Zimbabwe African National Union – Patriotic Front since independence in 1980 but Mugabe has been at the helm of the party since 1975. There is however no talk about him retiring from politics any time soon from within the ZANU-PF rank and file as shown by the party's endorsement of his name as the sole presidential candidate in the forthcoming 2013 presidential and parliamentary elections. The government owned newspapers are also silent about the need for a succession discussion to President Mugabe from both party presidency and state presidency. The private newspapers have, however found it important to discuss the succession to the president within the ZANU-PF party and have come up with a number of suggestions as to who could replace him should the need arise. It is from this background that the researcher looked at how the private print media are writing about with regard to the succession discourse to President Mugabe within the ZANU-PF party. The aim of the study is to find out whether the succession debate is real or just imaginary, whether there is infighting within the party and who could eventually succeed the president should the need arise. The researcher mainly used content and discourse analysis as well as hermeneutics of interpretation, interviews and diagnostic analysis. The researcher found out that much as the public print media is silent about the succession debate within the ZANU-PF hierarchy, the succession debate is real and imminent. The research also found out that the private print media believes there are factions lining themselves to succeed President Mugabe with the belief that whoever succeeds him at party level stands a better chance of eventually winning the state presidency as well. The findings indicated that a number of names were being forwarded for succession but two stood out clearly namely, Vice President Joyce Mujuru and defense minister Emerson Mnangagwa, although both of them categorically denied leading any form of faction for succession purposes. It was clear from the findings that the private media promoted the succession debate as a way of stabilizing ZANU-PF thereby helping opposition politics in the process.